KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN COFFEE SHOP - Waluyowati, Nur Prima; Bustomi, Muhammad Irsyad Gulam (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The aims of this study are to find out the cause and effect of service quality with customer satisfaction at the Omah Boto Coffee Shop based on the dimensions of service quality. The analysis obtained in this analysis examines the influence of the five dimensions of service quality, namely: tangibles (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee) and empathy (empathy) on customer satisfaction. Design/Methodology Quantitative methods were applied in this study. The distribution of questionnaires to 60 respondents was used to evaluate customer satisfaction about service quality at coffee shops and analyze data using multiple linear regression to determine the effectiveness of service quality on customer satisfaction. The findings examine that of the five dimensions of service quality, all have an influence on customer satisfaction, but only the assurance dimension has a major impact on customer satisfaction at Omah Boto Coffee shop. The results of this study can be used as a reference in the future related to service quality. The results of this study can also be a source of reference in increasing knowledge about the quality of service in the culinary field in Tuban City. The results of this study can also be input for the Omah Boto Coffee shop in providing services to shop customers.